Financial Leverage and Financial Performance in the Tertiary Sector: Partial Least Square- Multi-Group Analysis (PLS-MGA) - Nur Ainna Ramli , Ahmad Fadly Nurullah bin Rasedee (International Journal of Advanced Science and Technology, 2020)
We examine the comprehensive simultaneous relationship between countries, tertiary sector,financial leverage and firm financial performance. Most researchers routinely control for theindustry or the country as a dummy variable in order to test how the firm financial leverageaffect firm financial performance. However, the significant difference in the tertiary sector and,if there is, how the tertiary sector is different across countries, namely Malaysia and Indonesiahave not extensively examined. Therefore, from the methodological standpoint, the PLS-SEMprocedures and, as an extension, the PLS-MGA approach would make a valuable difference tocurrent knowledge, especially from the perspectives of the capital structure theory. We test theequality of coefficient effects using Partial Least Square of Multi-group analysis (PLS-MGA)between country comparisons for tertiary sector of the economy. The data sample consists of 13subsectors with the total final sample of 2720 for Malaysian and Indonesian tertiary sectors. Theresult reveals that there are few firm-country attributes to financial leverage and financialperformance are differ across countries. However, we find that the Malaysian and Indonesiantertiary sector shows consistent equal effects in their financial leverage and firm financialperformance